PELATIHAN PENYUSUNAN MODUL AJAR BERBASIS KURIKULUM MERDEKA BAGI GURU SMK PELAYARAN PERMATA ILMU MAROS DALAM MENDUKUNG PEMBELAJARAN - Munirah; Asfiati; Sartika, Dewi (Jurnal Pengabdian Indonesia (JPI), 2025)
The Independent Curriculum provides flexibility for educators to design learning that suits the characteristics of students and the needs of the world of work, especially in Vocational High Schools (SMK). However, there are still many teachers who have difficulties in understanding and compiling teaching modules that are in accordance with the principles of the Independent Curriculum. This community service aims to increase the capacity of teachers at SMK Pelayaran Permata Ilmu Maros in developing teaching modules that are contextual, adaptive, and oriented towards differentiated learning. The activity was carried out through intensive training and mentoring, including material on learning outcomes (CP), learning objectives (TP), learning objectives (ATP), and the integration of the Pancasila Student Profile. The implementation method consists of interactive lectures, group discussions, hands-on practice, and evaluation of participants' work. The results of the activity showed that there was an increase in teachers' knowledge and skills in compiling teaching modules that are relevant to the conditions of students and the shipping skills program. This activity makes a real contribution to supporting the implementation of the Independent Curriculum and improving the quality of learning in the vocational school environment.